Jalili Syndrome - Mian Muhammad Shafiq, Tayyaba Gul Malik, Muhammad Khalil, Shoaid Alam Shah (Pakistan Journal of Ophthalmology, 2016)
A thirty years old Pakistani male was referred from University of Lahore, Pakistan for clinical evaluation and interpretation of his ERG. Clinical examination revealed Cone – Rod dystrophy. Systemic examination showed discolored and abnormally shaped teeth. The patient was otherwise mentally and physically normal. His ERG showed Scotopic (rod responses) within upper normal limits in right eye while markedly reduced in the left eye. Scotopic rod and cone combined responses (indicating generalized retinal functions) were also decreased. Photopic (cone responses) were reduced in both eyes, with more marked fall in the left eye as compared to the right eye. Key Words: Rod-cone dystrophy, amelogenesis imperfect, Electro-retinogram, pigmentary retinopathy